Simplicity of Form: a tale of two cathedrals and interiors lost?: Hamilton Founders Memorial Theatre (1962) and St Joseph's Catholic Church Morrinsville (1964) - Kellaway, Laura (Architectural History Aotearoa, 2022)
St Joseph's Catholic Church, Morrinsville, was designed in 1958-62 by Doug Angus of Angus, Flood & Griffiths of Hamilton. Built in 1964-65, the design was radical, had simplicity in form both externally and internally. The simple external upturned parabola defied the level of innovation and detailing, creating both the exterior and interior form with the use of pre-stressed concrete ribs, and pre-cast panels between. The parabolic form was 49' 6" in height, designed by engineer Thomas Flood. The 8,000 sqft church accommodated 600 people. It was said to be New Zealand's largest single-pour concrete roof of the time. The Modernist interior was of a grand scale with the specially-designed fittings - only seen by parishioners. And this was part of its demise. The scale was for a cathedral not small-town New Zealand. Regionally significant in terms of architecture and engineering technology, an iconic Waikato church, and the work of an important Modernist architect and engineer, yet it was demolished in 2014. In the Waikato, at the same time as the church was being designed, the new regional theatre and "town hall" was on the drawing board of architect Aubrey de Lisle, of White, de Lisle and Jenkins of Hamilton. The Founders Memorial Theatre opened in November 1962, inspired by Coventry's Belgrade Theatre, which was the first civic theatre built in Great Britain after World War Two. The 1,249-seat theatre, built a decade before Christchurch Town Hall, has hosted international performers of note to local theatre and music productions within its "gently sloping wood panelled confines." Jazz great Louis Armstrong arrived for shows on 20 March 1963, but due to payment issues he almost didn't play at all. From Louis Armstrong to Cilla Black in 1965, to the home of the Finns, the theatre for over 60 years has been the focus of many from the new teenagers of the 1960s to classical music and the performance of the young ballet students. Closed in 2016 from lack of maintenance and ongoing strengthening, with the Hotere mural removed for the new Waikato Theatre, the interior now only used in the dark for police exercises as its fate awaits. Two very different cultural interiors – a cathedral for faith and a "cathedral" for performance – a church and a theatre.